Should You Allow Your Agent to Become Your Competitor? On Non-Compete Agreements in Employment Contracts - Matthias Kräkel; Dirk Sliwka (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We discuss a principal-agent model in which the principal has the opportunity to include a non-compete agreement in the employment contract. We show that not imposing such an agreement can be beneficial for the principal as the possibility to leave the firm generates implicit incentives for the agent. The principal prefers to impose such a clause if and only if the value created is sufficiently small relative to the agent's outside option. If the principal can use an option con- tract for retaining the agent, she will never prefer a strict non-compete agreement.
urn:nbn:de:bvb:19-epub-13452-9
Keywords: D21; D86; J3; K1; M5; 330; fine; incentives; incomplete contracts; non-compete agreements; option contract